Institutionalizing Health Technology Assessment in Ghana: Enablers, Constraints, and Lessons - Augustina Koduah; Jessica Anim Boadi; Joycelyn Naa Korkoi Azeez; Brian Adu Asare; Saviour Yevutsey; Martha Gyansa-Lutterodt; Justice Nonvignon (Taylor & Francis Group, 2023)
Health Technology Assessment (HTA) has been institutionalized in Ghana with structures, processes, and methods. This paper identifies and analyzes the policy players involved; the way in which issues were framed; and the manner in which administrative structures were used to set the agenda for, adopt, and implement HTA. It shows that the Ministry of Health, supported by other players, led HTA agenda-setting through training activities and discussions on evidence of selection pharmaceuticals, medical devices, and other health-related technologies. HTA was then captured in a health sector aide memoire that summarized the decisions made at a national health summit. In implementing the HTA policy, technical working groups and a steering committee were constituted to provide recommendations to the minister of health on high-level decisions. The ability of agenda influencers to maneuver existing administrative and bureaucratic structures, align them with national strategic goals, and sustain HTA implementation enabled Ghana to institutionalize HTA. Limited financial support and a dearth of in-country expertise are being addressed through capacity building and funding. To ensure early national buy-in and uptake, policy makers and agenda influencers need to understand each country's health system and align HTA with national policy decision-making processes.